Relationship Between Physical Activity Level and Primary Care Costs in Older Diabetic Patients From a Middle-Size Brazilian City: An Eight-Year Follow-Up Study - Koyama, Kelly Akemi Kikuti [UNESP]; Araujo, Monique Yndawe Castanho [UNESP]; Morais, Luana Carolina de [UNESP]; Lemes, Italo Ribeiro [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Turi-Lynch, Bruna Camilo; Sarti, Flávia Mori; Delacosta, Thais Cristina [UNESP]; Monteiro, Henrique Luiz [UNESP]; Codogno, Jamile Sanches [UNESP] (Frontiers, 2025)
Objectives: Physical activity and costs have been consistently related each other, but mostly in cross-sectional investigations. This study aims to investigate the relationship between changes in physical activity level and changes in healthcare costs among older diabetic adults in an 8-year follow-up study. Methods: The study followed 151 diabetic adults ≥50 years of age, for a period of 8 years, who were patients of Basic Health Care Units in the city of Bauru (Brazil). Medical records were consulted to obtain information on healthcare costs. Physical activity level was assessed through an interview. Data analysis included descriptive statistics, analysis of variance, and linear regression. Results: Participants who increased leisure-time physical activity from 2010 to 2018 accumulated less healthcare costs from 2020 to 2018. The magnitude of the relationship was small (r = −0.233 [95% CI: −0.379 to −0.076]). Conclusion: In summary, among diabetic patients, to increase leisure-time physical activity from 2010 to 2018 was inversely related to the amount of healthcare costs spent over the same period of 8 years.
Keywords: diabetes mellitus; epidemiology; health care costs; physical activity; primary care